Cloning gibberellin dioxygenase genes from pumpkin endosperm by heterologous expression of enzyme activities in Escherichia coli - Lange, Theo (The National Academy of Sciences of the USA, 1997)
Gibberellin (GA) plant hormones are biosynthesized via complex pathways, the final steps of which are catalyzed by 2-oxoglutarate-dependent dioxygenases. Here, the cloning of two such enzymes, the GA 7-oxidase and the GA 20-oxidase, is reported using a novel approach, namely, by screening for GA dioxygenase activities expressed as T7 gene 10 fusion proteins in recombinant Escherichia coli. In vitro translation products of mRNA from endosperm of immature pumpkin seeds contained three GA dioxygenase activities, including 7-oxidase, 20-oxidase, and 3β-hydroxylase. A cDNA expression library was prepared from the endosperm mRNA in λMOSElox. An aliquot of the amplified library was converted to plasmids in vivo and used for transformation of E. coli BL21(DE3), which thereafter expressed recombinant fusion proteins containing 7-oxidase, 20-oxidase, and 3β-hydroxylase activities. By screening for specific GA dioxygenase expression, clones harboring 7-oxidase and 20-oxidase cDNA were isolated. The ORF of the 7-oxidase cDNA is 945 bp long, encoding for 314 amino acid residues with a calculated M(r) of 35,712 and pI of 5.7. Recombinant GA 7-oxidase oxidizes GA(12)-aldehyde to GA(12) and GA(14)-aldehyde to GA(14). Evidence was obtained for further metabolism of GA(12) by the 7-oxidase to four products, two of which are monohydroxylated GA(12). The ORF of the 20-oxidase is—apart from seven changes, resulting in four amino acid substitutions—identical to the 20-oxidase cDNA previously cloned from pumpkin cotyledon mRNA; both 20-oxidases have the same catalytic properties.